Research on the Integration of Cultural Tourism Industry Driven by Digital Economy in the Context of COVID-19—Based on the Data of 31 Chinese Provinces - Li, Xiangyin; Liang, Xueping; Yu, Ting; Ruan, Sijia; Fan, Rui (Frontiers in Public Health, 2022)
This paper examines the impact of digital economy on the integration of China's cultural tourism industry in the context of COVID-19 by measuring the integration degree of cultural tourism industry as a substitute variable of cultural tourism integration. The empirical study found that the development of digital economy during the COVID-19 pandemic did promote the integration of China's cultural tourism industry, and compared with year 2019, the digital economy has strengthened the integration of cultural tourism industry. During the COVID-19 pandemic, the development of digital economy has promoted the integration of China's cultural tourism industry, and the positive effect of digital economy on the integration of China's cultural tourism industry has gradually strengthened compared to previous ones. The digital economy has played a mediating role in the impact of COVID-19 on the integration of China's cultural tourism industry.